Dinamika Pengambilan Keputusan Bawaslu Dalam Menangani Laporan Kecurangan Pemilu: Analisis Teori Agregasi Keputusan - Dewi, Puspita Dewi Lestari; Alfhatan Dwi Sujidan; Alida Putri Nurhaliza; Inayah Fauziah (Program Studi Ilmu Pemerintahan Universitas Islam Raden Rahmat Malang, 2024)
Fraud reports in the context of general elections are a very important issue in maintaining the integrity and legitimacy of the democratic process. As an election supervisory institution at the district level, the Karawang Regency Election Supervisory Agency (Bawaslu) has a crucial role in handling fraud reports that may occur during the election process. Not many previous studies have used decision aggregation theory to analyze how Bawaslu makes decisions in handling reports of election fraud. This study aims to conduct an in-depth analysis of the development of reports of election fraud received by Bawaslu Karawang Regency. This research uses a qualitative method with a case study approach to explore reports of election fraud to the General Election Supervisory Agency (Bawaslu) of Karawang Regency using decision aggregation theory. Through this article, it is hoped that it can make a positive contribution in increasing understanding and awareness of the importance of handling reports of election fraud by Bawaslu Karawang Regency in order to maintain integrity and public trust in the democratic process at the regional level.